2021
DOI: 10.3389/fphys.2021.743094
|View full text |Cite
|
Sign up to set email alerts
|

The Chloride Conductance Inhibitor NS3623 Enhances the Activity of a Non-selective Cation Channel in Hyperpolarizing Conditions

Abstract: Handbooks of physiology state that the strategy adopted by red blood cells (RBCs) to preserve cell volume is to maintain membrane permeability for cations at its minimum. However, enhanced cation permeability can be measured and observed in specific physiological and pathophysiological situations such as in vivo senescence, storage at low temperature, sickle cell anemia and many other genetic defects affecting transporters, membrane or cytoskeletal proteins. Among cation pathways, cation channels are able to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Automated patch-clamp on the SyncroPatch 384PE (Nanion Technologies, Munich, Germany) was used to measure Gárdos activity, with a modified protocol previously described [ 14 ]. Briefly, after three washes with PBS and upon cell catch, external recording solution was added to the wells followed by 10 µM NS3623 (a powerful chloride channel inhibitor [ 15 ]), 10 µM NS309 (Alomone labs, Jerusalem, Israel), 5 µM TRAM-34 (a specific Gárdos channel inhibitor, Tocris, Bristol, UK), and 30 µM GdCl 3 (a generic non selective cation channel inhibitor, Sigma-Aldrich, St. Louis, MO, USA). Internal solution (in mM): 10 KCl, 110 KF, 10 NaCl, 10 EGTA, and 10 HEPES/KOH (pH 7.2).…”
Section: Methodsmentioning
confidence: 99%
“…Automated patch-clamp on the SyncroPatch 384PE (Nanion Technologies, Munich, Germany) was used to measure Gárdos activity, with a modified protocol previously described [ 14 ]. Briefly, after three washes with PBS and upon cell catch, external recording solution was added to the wells followed by 10 µM NS3623 (a powerful chloride channel inhibitor [ 15 ]), 10 µM NS309 (Alomone labs, Jerusalem, Israel), 5 µM TRAM-34 (a specific Gárdos channel inhibitor, Tocris, Bristol, UK), and 30 µM GdCl 3 (a generic non selective cation channel inhibitor, Sigma-Aldrich, St. Louis, MO, USA). Internal solution (in mM): 10 KCl, 110 KF, 10 NaCl, 10 EGTA, and 10 HEPES/KOH (pH 7.2).…”
Section: Methodsmentioning
confidence: 99%
“…It has been widely reported that the activation of PIEZO1 by Yoda1 induces a cell dehydration accompanied by a reversal of sodium and potassium gradients due to its nature of being a non-selective cation channel ( Monedero Alonso et al, 2021 ; Pérès et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…27,44,45 Specifically to human RBCs, experimental studies also support the involvement of ion transport pathways in the osmotic response of RBCs as the ion flux rates may be high enough to result in considerable KCl loss within ~15 minutes 67 (action equivalent to RVD response) or increase of intracellular Na in 30 minutes (RVI). 50 Furthermore, wholecell recordings of 68 to 500 pico-siemens cation conductances were reported, 51,68,69 corresponding to about a 3 to 4 order increase compared to the normal isotonic value. 70 This experimental observation supports the relatively high rate of predicted NaCl loading occurring only via physiological ion transport pathways (consult Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…48 The presence of shrinkage-activated cation channels (classified as HICCs) in the RBC plasma membrane has been confirmed. 49 The capacity of human RBCs to substantially increase the cation permeability was reported several times [49][50][51][52] with even several-order increases being observed. 53 It is suggested here that HICCs might be a major contributor to the RVI response, which is hypothesized to cause sodium influx (coupled with an influx of chlorine ions) under hypertonic conditions -emphasizing the physiological route for the salt loading.…”
Section: Cell Physiology and Cell Volume Regulationmentioning
confidence: 99%
See 1 more Smart Citation